РЕШЕНИЕ ЗАДАЧИ ПРОДОЛЖЕНИЯ МАГНИТНОГО ПОЛЯ С ЦИЛИНДРИЧЕСКОЙ ПОВЕРХНОСТИ ПРИ ПОМОЩИ ФУНКЦИИ ГРИНА - Коновалов, О.Я.; Михайлов, В.М.; Петренко, Н.П. (Інститут електродинаміки НАН України, Київ, 2016)
The method for solving of the problem of continuing magnetic flux from cylindrical surface with a given distribution of the tangential component of the magnetic induction is developed. The using of circular infinitely thin conductors with the currents and the responding of Green’s function is proposed. An example of determining the profile of massive single-turn solenoid, for generating given induction distribution of pulsed magnetic field on surface of the long cylindrical shell with sharp skin effect in conductors. References 7, figures 3.